Warts - Mirror of Internal Diseases, Conquer with General and Homoeopathic Measures (Homoeopathy for All, 2024)
Wart is a small growth with a rough  texture that can appear anywhere  on the body. It can look like a solid  blister or a small cauliflower. A small,  fleshy bump on the skin or mucous  membrane. Warts are benign skin  growth that appears when a virus  infects the top layer of the skin. And  the viruses that cause warts are called  human papillomavirus (HPV). Warts  can apply anywhere on the skin and  are noticed mostly on the hands and  feet. They are highly contagious and  spread to other areas of the skin as  well as spread to others when shared  towels, razors etc are used. The skin  is where internal diseases manifest.  This article provides an overview  of the aetiology, diagnosis, and  appropriate general & homoeopathic  management of this disorder.
Keywords: mucous; cervical cancer; aetiology